Vegetation Composition and Carbon Storage Potential at Tree and Pole Levels in the Gunung Leuser National Park Area, Bukit Lawang, Bahorok District, Langkat Regency, North Sumatra - Siregar, Etti Sartina; Aththorick, T Alief; Atni, Oky Kusuma; Nasution, Ahmad Luthfi Abdillah; Hermansyah; Lubis, Putri Amelia; Pardosi, Sinta R; Mustaqilla, Safira; Mardhatillah, Siti (International Journal of Ecophysiology, 2025)
Forests play a crucial role in environmental, economic, and social sustainability by storing carbon and mitigating climate change. This study aimed to assess the vegetation composition, diversity, and carbon storage in Gunung Leuser National Park, Bukit Lawang, North Sumatra. Fieldwork, conducted using purposive and nested sampling methods, recorded 11 families and 14 plant species with 27 individuals at the tree growth level, and 11 families and 16 plant species with 30 individuals at the pole growth level. The Burseraceae family dominated tree-level composition (29%), while the Phyllanthaceae family dominated pole-level composition (28%). The highest Important Value Index (IVI) was Santiria rubiginosa (36.09%) for trees and Gironniera nervosa (55.46%) for poles. The Shannon-Wiener Diversity Index (H’) was 2.45 for trees and 2.53 for poles, with evenness values (E) of 0.93 and 0.91, respectively. The total biomass was 120.240 tons/ha, with stored carbon amounting to 55.310 tons C/ha. To better estimate carbon storage potential, further research should cover larger areas and include biomass components like litter and dead wood.